2009
DOI: 10.5194/acp-9-2113-2009
|View full text |Cite
|
Sign up to set email alerts
|

What would have happened to the ozone layer if chlorofluorocarbons (CFCs) had not been regulated?

Abstract: Abstract. Ozone depletion by chlorofluorocarbons (CFCs) was first proposed by Molina and Rowland in their 1974 Nature paper. Since that time, the scientific connection between ozone losses and CFCs and other ozone depleting substances (ODSs) has been firmly established with laboratory measurements, atmospheric observations, and modeling studies. This science research led to the implementation of international agreements that largely stopped the production of ODSs. In this study we use a fully-coupled radiation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 47 publications
12
155
4
1
Order By: Relevance
“…EESC is a modeled representation of the amount of chlorine and bromine in the atmosphere available to destroy stratospheric ozone at a given time and location, based on measurements of ozone-depleting substances in the troposphere, age of air, and the fractional release rates of chlorine and bromine from various chemical constituents (Newman et al, 2007). Our best current understanding, as represented in chemistry climate models, predicts that stratospheric ozone varies linearly with EESC (e.g., Newman et al, 2009). Therefore, when we fit a data record using the EESC as a regression parameter, we are testing the degree to which the data are following the model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…EESC is a modeled representation of the amount of chlorine and bromine in the atmosphere available to destroy stratospheric ozone at a given time and location, based on measurements of ozone-depleting substances in the troposphere, age of air, and the fractional release rates of chlorine and bromine from various chemical constituents (Newman et al, 2007). Our best current understanding, as represented in chemistry climate models, predicts that stratospheric ozone varies linearly with EESC (e.g., Newman et al, 2009). Therefore, when we fit a data record using the EESC as a regression parameter, we are testing the degree to which the data are following the model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that during the 1980s the ozone hole over Antarctica expanded rapidly, this expansion slowed in the 1990s. In the last few years this expansion and ozone loss rates have appeared to level off (Newman et al, 2009;Austin et al, 2010). Figure 5 shows an example of ozone maps over the Antarctic during the ozone hole period.…”
Section: Iasi Ozone Retrievalsmentioning
confidence: 99%
“…Ozone is calculated using the Goddard Space Flight Center (GSFC) (Fleming et al, 2007;Newman et al, 2009) and the NOCAR (Solomon et al, 1998;Portmann et al, 1999) interactive 2-D models with 2006 Jet Propulsion Laboratory (JPL) rates (Sander et al, 2006). Both models successfully capture the processes important for calculating globally averaged total ozone.…”
Section: Ozone Calculationsmentioning
confidence: 99%